Language Technologies: a Happy Marriage between Linguistics and Informatics - Tadić, Marko (2009)
This keynote lecture presented the current state of relations between (computational) linguistics and information sciences. The processing of language data has its specific requests and at the same time this specificity is changing the way that traditional information processing tasks (such as information retrieval, document retrieval, information extraction, text-mining, etc.) have been done. The issues within artificiall intelligence dealing with processing of natural languages are also mentioned.